Estado nutricional vitamínico a e sua relação com a anemia em idosos: um estudo de base populacional - Barbosa, Fernanda Patricia Torres (2011)
The deficiencies of iron and vitamin A play a greater role in epidemiological studies and in formulating public policies of health, food and nutrition. Anemia is the most prevalent hematologic disorder that affects the elderly population. In this context, this study aimed the investigation of the relationship between the nutritional status of vitamin A and anemia in the elderly population, seeking to contribute to a better understanding of these relationships. It was adopted a cross-sectional epidemiological design, population-based, using a stratified sample representative of the elderly population in the municipality of João Pessoa, Northeast, Brazil. The study included 160 individuals between 60 and 90 years, from different socioeconomic levels, with or without chronic degenerative diseases and in use or not of medications and supplements. Questionnaires were applied to obtain socioeconomic, demographic, epidemiological and food intake (QQFCA). Analyses of serum retinol by High Performance Liquid Chromatography Resolution and hemoglobin by Electrical Impedance. To verify the relationship between two variables used the Spearman Correlation Coefficient. It was evident in most individuals of various socioeconomic levels, appropriate values of serum retinol (1,78 ± DP 0,68) and hemoglobin (13,00 ± DP 1,42) and high rates of morbidity (79,63%). There was significant correlation between low hemoglobin and education (p=0,0222), consumption of meat and hemoglobin (p=0,0040) and between dietary iron intake and dietary intake of vitamin A, meats, vegetables and fiber (p<0,0001, respectively). Even in the absence of correlation between hemoglobin, serum retinol, and food consumption of vegetables, fruit and fiber are highlighted in this study, the influence of meat consumption in hemoglobin, but also the food consumption of vitamin A, meat, vegetable and fiber consumption of dietary iron, which may have contributed to the adequate levels of serum retinol and hemoglobin in this population.